Discontinuation rates and predictors of Medical Cannabis cessation for chronic musculoskeletal pain - Mohammad Khak; Sina Ramtin; Juliet Chung; Asif M. Ilyas; Ari Greis (PLoS ONE, 2025)
Medical cannabis (MC) is increasingly used as a treatment for chronic musculoskeletal pain, but there is limited data on factors influencing its discontinuation. This study aims to investigate the rates of MC discontinuation and explore factors influencing it in patients with chronic musculoskeletal pain. A retrospective analysis was conducted on 78 patients certified for medical cannabis over a 2 year period. Patient demographics, pain origin, and Global Physical Health (GPH) and Global Mental Health (GMH) scores were collected before intervention. Discontinuation rates were measured at three-month and one-year follow-up. Statistical analyses, including Fisher’s Exact Test and two-sample t-tests, were performed to assess associations between variables and discontinuation. The overall discontinuation rate of MC use was 57.9% at one year, with 44.7% of patients discontinuing within the first three months. Older age was significantly associated with higher discontinuation rates. Pain origin categories did not significantly differ between those who discontinued and continued MC use, although a higher proportion of patients in the discontinued group reported low back pain. No significant differences were observed in baseline GPH and GMH scores between the two groups. This study demonstrates a high discontinuation rate of MC use in patients for chronic musculoskeletal pain. The absence of significant differences in pain origin or baseline health scores suggests that factors beyond pain location or general health may contribute to the decision to discontinue MC. Further research is needed to explore the long-term effects of MC on pain management and patient outcomes.